2017
DOI: 10.1016/j.xphs.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment With Rifampicin and Tyrosine Kinase Inhibitor Dasatinib Potentiates the Inhibitory Effects Toward OATP1B1- and OATP1B3-Mediated Transport

Abstract: Current studies determined the effects of pretreatment with rifampicin, an organic anion-transporting polypeptide (OATP) inhibitor, and the tyrosine kinase inhibitor dasatinib on OATP1B1- and OATP1B3-mediated transport, and to evaluate the OATP-mediated drug-drug interaction (DDI) potential of dasatinib using the static R-value and dynamic physiologically-based pharmacokinetic models. Rifampicin and dasatinib pretreatment significantly decreased OATP1B1- and OATP1B3-mediated transport. Rifampicin pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 54 publications
5
51
1
1
Order By: Relevance
“…Assuming almost complete inhibition of transporter-mediated uptake of pitavastatin at 1 mM rifamycin SV (Thakare et al, 2017), this uninhibited uptake should represent the contribution of passive diffusion to total cellular uptake, which in this case was higher compared with estimates obtained by mechanistic modeling of kinetic data done over short incubation times. Such incomplete inhibition of uptake for pitavastatin has previously been reported in monkey hepatocytes using rifampicin and cyclosporine (Takahashi et al, 2013) and in human hepatocytes using rifampicin (Pahwa et al, 2017) and may reflect the combination of passive diffusion and involvement of transporter uptake not inhibited by these inhibitors.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Assuming almost complete inhibition of transporter-mediated uptake of pitavastatin at 1 mM rifamycin SV (Thakare et al, 2017), this uninhibited uptake should represent the contribution of passive diffusion to total cellular uptake, which in this case was higher compared with estimates obtained by mechanistic modeling of kinetic data done over short incubation times. Such incomplete inhibition of uptake for pitavastatin has previously been reported in monkey hepatocytes using rifampicin and cyclosporine (Takahashi et al, 2013) and in human hepatocytes using rifampicin (Pahwa et al, 2017) and may reflect the combination of passive diffusion and involvement of transporter uptake not inhibited by these inhibitors.…”
Section: Resultssupporting
confidence: 58%
“…For example, rifampicin in vitro K i values were shown to be several fold higher than the in vivo K i estimated from the clinical DDI data using mechanistic modeling Barnett et al, 2017;Yoshikado et al, 2017). In addition, a number of studies demonstrated potentiation of OATP1B inhibition following preincubation with the inhibitor, trend particularly evident for cyclosporine (Amundsen et al, 2010;Gertz et al, 2013;Izumi et al, 2015;Takahashi et al, 2016;Pahwa et al, 2017) and incorporated in the recent Food and Drug Administration DDI guidance document (https://www.fda.gov/downloads/ Drugs/Guidances/UCM581965.pdf). Although the clinical DDIs with cyclosporine are well recovered with the IC 50 obtained following preincubation (Gertz et al, 2013), there is limited understanding of the significance of preincubation in predicting DDIs of other inhibitor drugs.…”
Section: Introductionmentioning
confidence: 98%
“…RIF model‐based in vivo Ki values were 3–4‐fold lower compared with in vitro parameters obtained in human hepatocytes with the corresponding probes and following preincubation with inhibitor ( Figure b ). None of the previous literature RIF inhibition studies considered the preincubation effect, with the exception of the current analysis and recent study . Although the shift in RIF inhibition potency with preincubation was not as prominent as reported in the case of cyclosporine, it reduced the disconnect between in vitro and in vivo inhibition parameter estimates.…”
Section: Discussioncontrasting
confidence: 53%
“…The simulation was based on a two period one‐way crossover study design where in the first period plasma/urine samples of CPI are observed under baseline condition and following a period of washout the same subjects received a single dose of 600 mg RIF and plasma/urine samples of CPI were collected again for analysis. Power curves were calculated for each modified I/Ki ratio by performing a one‐sample paired t ‐test on the ratio of logarithmic transformed AUC following simulation at predefined sample sizes . At each sample size, the simulation and tests were repeated 5,000 times and the power of the test was calculated as the proportion of the simulations during which the null hypothesis was rejected at the significance level (0.05 and 0.01).…”
Section: Methodsmentioning
confidence: 99%
“…In vitro, in vivo, and clinical data were extracted. The details of the articles were inserted into tables (shown in Supplementary Materials Tables S1–S9 ) [ 43 , 44 , 45 , 46 , 47 ] For alectinib, avapritinib, baracitinib, binimetinib, brigatinib, cobimetinib, dacomitinib, encorafenib, erdafitnib, fedratinib, gilteritinib, ibrutinib, laroctrectinib, lorlatinib, midostaurin, pexidartinib, ponatinib, trametinib, and zanbrutinib no published reports were found. In data collected for 17 TKIs, the results of the published data were largely inconsistent in that some of the published results for a given TKI identified the TKI as an inhibitor of OATP1B1 or OATP1B3, while other sources identified it expressly as a non-inhibitor.…”
Section: Effects Of Tkis On the Function Of Oatp1b1 And Oatp1b3mentioning
confidence: 99%